STRATEGI PEMBELAJARAN BAHASA ARAB DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS VII SMP ISLAM SUNAN GIRI WAGIR MALANG - Nur Cholis; Anwar Sa’dullah; Ibnu Jazari (VICRATINA, 2020)
Background this research is based on a phenomenon that not all learning will achieve the desired objectives. Interest is one of the internal factors of students that greatly influences learning success. High interest in learning will make students enthusiastic in learning and can easily achieve the competencies to be achieved. To motivate students' interests, certain strategies in learning are needed. So that what will be learned can be directly accepted easily by students in Sunan Giri Wagir Islamic Middle School. The study uses qualitative research and descriptive research types, which describe completely with what is objective in accordance with the data collected. Data collection is done by observation, interviews and documentation. In describing the results of the interview, the author uses observation and documentation as a reinforcement of the data obtained from the interviews of the learning strategies used by Arabic language teachers in increasing student interest in learning. The research informants were the school principal, Arabic language teacher, and Islamic Junior High School students, Sunan Giri Wagir.